PENGEMBANGAN MODEL MCDM-ANP (ANALYTIC NETWORK PROCESS) DALAM METODE TEKNOMETRIK UNTUK PENILAIAN KANDUNGAN TEKNOLOGI - Ciptomulyono, Udisubakti (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2010)
Technometric is one of technology component contribution measurement method that consists of technoware, humanware, inforware and orgaware technology (ES-CAFE). The usage of AHP (Analytic Hierarchy Proces) method has weaknesses in measuring the assumption of cluster criteria independency and other decision elements. This research analyzed the possibility of ANP (Analytic Network Process) implementation in technometric method for handling dependency relation among the technology components. ANP Method is AHP development method using feedback approach and decision components that are arranged in network shape not in linear hierarchy, so it is able to count interdependency relation between the technology component and elements in industrial system more completely. For testing the validation of a ceramic industrial object that will be used as an object of technology intensity measurement. The research result shows that measured technology component or almost all of the elements inside make multi direction relation, means there is an interdependency relation between the component and the elements. This technology coefficient contribution for industry is 0.81, with technoware component contribution 0.86, humanware 0.88, orgaware 0.8, and inforware 0.69.